Information on the investor relations websites – How to study its usefulness? A research proposal - Sabelfeld, Svetlana (Proceedings of Pragmatic Constructivism, 2011)
This paper can be seen as a preliminary research proposal to my continued PhD project. My expectation is therefore to receive your feedback concerning the whole proposal, and, specifically, I would appreciate if you could suggest how to conceptually frame this project; and also if you could provide me with your feedback concerning methodology.